A study on knowledge, perception, attitude and barriers among nursing students of Ganesh Das Government Maternal and Child Health Hospital, Shillong: a cross-sectional study on fertility - Hynniewta, Barry Cooper; Marbaniang, Kathrina; Kharbuli, Restitula; Kurbah, Ronald Eleazer; Kumari, Esha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The inability to get pregnant after a year of unprotected sex is known as infertility. Loneliness and emotional distortion are quite common psychological effects in this population. The causes of female infertility include factors like ovulatory disorders, tubal adhesion, uterine fibroid, endometriosis, STIs, diabetes and cancer. Male infertility can be brought on by low sperm count, low sperm motility, genetic disorders, ejaculatory dysfunctions, testicular injuries or surgeries, excessive obesity, and lifestyle variables like smoking, drinking alcohol and drug usage. The aim was to assess the fertility awareness of nursing students of a tertiary care hospital and its association with demographic factors. Methods: This cross-sectional study targeted nursing students at Ganesh Das Government MCH Hospital having 154 nursing students. A 33-item FA questionnaire was developed to determine the FA score based on accurate responses. Correct answers scored 1, incorrect scored 0. Participants categorized into low (30%), moderate (31-60%), and high (>61%) FA levels. R-software was used for data analysing. Results: Out of 154 nursing students 59.09% were aware of their fertility days. 87.01% were sexually active and 74.68% had normal menses. Half of the populations were dissatisfied with their knowledge of fertility. 76.62% responds due to communication barrier. Year of study was the only variable to have significant difference with fertility awareness (FA) (p value<0.05). Conclusions: Knowledge of fertility awareness was found to be sufficient however, male infertility still lacks. Role of government, primary and specialized health care workers need to emphasize on fertility at an early age to prevent high rate of undiagnosed infertility.